THE PHENOMENON OF ISLAMIC JOKES ON SOCIAL MEDIA: BETWEEN ENTERTAINMENT AND THE INTERNALIZATION OF ISLAMIC EDUCATION VALUES - Muhammad Ni’am Agustian (SOSIOEDUKASI, 2026)
The phenomenon of Islamic jokes on social media has become increasingly popular alongside the rapid growth of digital platforms as spaces for expression and education. This study aims to analyze the role of Islamic jokes as a form of entertainment as well as a medium for the internalization of Islamic Religious Education (IRE) values. This research employs a qualitative descriptive approach through content analysis of Islamic humor-themed posts on social media platforms such as Instagram, TikTok, and YouTube, with a specific focus on TikTok. The findings indicate that Islamic jokes serve two primary functions. First, they function as a light, contextual, and easily accessible form of entertainment for the digital generation. Second, they possess the potential to internalize Islamic values through moral messages, character development, and the creative delivery of religious teachings. Nevertheless, the study also identifies the risk of meaning distortion and oversimplification of religious teachings when such content is not accompanied by proper understanding. This research emphasizes that Islamic jokes can serve as an effective educational medium when presented proportionally, ethically, and in accordance with Islamic legal and moral principles. These findings are expected to provide references for educators, content creators, and researchers in developing Islamic education and da‘wah strategies that are relevant to contemporary social media culture.